Ensley, Mimi. 2023. Difficult Pasts. Post-Reformation Memory and the Medieval Romance. Manchester: Manchester University Press. Pp. 242. ISBN 9781526157898 - Boffey, Julia (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Ensley, Mimi. 2023. Difficult Pasts. Post-Reformation Memory and the Medieval Romance. Manchester: Manchester University Press. Pp. 242. ISBN 9781526157898.